Răspuns :
(a+b+c)/3 = 2,1 => a+b+c = 3x2,1 = 6,3
(a+b)/2 = 2,5 => a+b = 2x2,5 = 5
c = 4a
Scadem a doua relatie din prima:
a+b+c-a-b = 6,3-5
c = 1,3
Dar a = c:4 = 1,3:4
a = 0,325
a+b = 5 +> b = 5-a
b = 5-0,325
b = 4,675
(a+b)/2 = 2,5 => a+b = 2x2,5 = 5
c = 4a
Scadem a doua relatie din prima:
a+b+c-a-b = 6,3-5
c = 1,3
Dar a = c:4 = 1,3:4
a = 0,325
a+b = 5 +> b = 5-a
b = 5-0,325
b = 4,675
(a+b+c):3=2,1
(a+b):2=2,5
c=4a
a+b+c= 6,3
a+b=5
5+c=6,3
c=6,3-5
c=1,3
c=4a
a=1,3:4
a= 0,325
0,325+b=5
b= 5-0,325
b=4,675
sper ca te am ajutat
(a+b):2=2,5
c=4a
a+b+c= 6,3
a+b=5
5+c=6,3
c=6,3-5
c=1,3
c=4a
a=1,3:4
a= 0,325
0,325+b=5
b= 5-0,325
b=4,675
sper ca te am ajutat